Hearts of darkness: Pauw, J (1997) Into the heart of darkness: Confessions of Apartheid's assassins Cape Town: Jonathan Ball. ISBN 1-8684-058-2 pbk. 346 pages. - Earl-Taylor, Mike (PINS-Psychology in Society, 2026)
In a work of incisive investigative journalism, Jacques Pauw has explored the underworld of Apartheid's assassins and their reign of murder, torture and mayhem. His interpretative exploration manages to engage and draw out the shadowy central figures through in-depth interviews, transcripts of their own confessions, and archival, corroborative research from a wide range of sources. The book is structured into 21 chapters, each focusing on a particular assassin (e.g. Dirk Coetzee, Almond Nofemela, Ferdi Barnard, Andries Brood, et al.), and includes extensive notes and index, with a useful list of the mind-boggling acronyms that serve to mystify and alienate these accounts (e.g. the CCB, C1, DCC, SB, SAP, etc.). A must-read for all South Africans for its readability, thorough research and insight, the text is also suitable for use at university level in contemporary South African History, Sociology and Criminology The focus on the apparently sociopathic personalities of some of the interviewees makes it interesting to clinical / forensic applications of psychology, where deviant behaviour patterns are investigated.